Construction superintendent's operations manual - Levy, Sidney M. (McGraw-Hill, 2004)
Addresses 3 basic topics: administering construction contracts, supervising the construction process, and construction components and technology. This book provides guidance on a range of issues, including employee relations, construction quality, and safety. It also includes over 100 handy forms, sample letters, and checklists